Association of a congenital long QT syndrome type 1 with Takotsubo cardiomyopathy. Issue 8 (12th July 2016) - El‐Battrawy, Ibrahim; Behnes, Michael; Borggrefe, Martin; Akin, Ibrahim
Key Clinical Message: The occurrence of takotsubo cardiomyopathy in a patient with congenital long QT syndrome has rarely been described. This case report discusses the occurrence of a clinically overt takotsubo cardiomyopathy accompanied by congenital long QT syndrome type 1 in a female patient. Abstract : The occurrence of Takotsubo cardiomyopathy in a patient with congenital long QT syndrome has rarely been described. This case report discusses the occurrence of a clinically overt Takotsubo cardiomyopathy accompanied by congenital long QT syndrome type 1 in a female patient.